Effect of lipids and thermal processing on antioxidant activity of galangal seasoning, tom-kha paste extract - Naiyana Pengseng; Sunisa Siripongvutikorn (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The effect of lipids on antioxidant activities of tested antioxidants and the galangal seasoning, Tom-Kha paste extract were determined. The result showed that heating caused a decrease of DPPH scavenging activity of lauric acid but did not affected on ABTS scavenging activity of both lauric acid and virgin coconut oil. However, ABTS scavenging activity of p-hydroxycinnamic acid and the paste extract in both lauric acid and virgin coconut oil systems increased after thermal processing. In the system of lauric acid, peroxide value (PV) of almost mixtures was increased (p0.05) by heating. Thiobarbituric acid reactive substances (TBARS) of the mixtures were not significantly different (p0.05) after thermal processing while p-anisidine value (AV) of only lauric acid-gallic was enhanced after heating. The results showed that PV of virgin coconut oil added with all tested antioxidant was not changed after heating. TBARS of virgin coconut oil added with antioxidant samples seemed to slightly increase after heating. AV of virgin coconut oil with added gallic acid and the paste extract were not changed while AV of virgin coconut oil with added p-hydroxycinnamic acid and Trolox seemed to decrease after heating